POLA DAN DOMINASI KEKUASAAN OLIGARKI LOKAL PADA INDUSTRI PERTAMBANGAN DI KALIMANTAN TIMUR - Budiman; Daswati; Muhammad Nur Alamsyah (Jurnal Agregasi, 2025)
This study aims to uncover the patterns and dominance of local oligarchic power in the coal mining industry in East Kalimantan. Using a descriptive qualitative approach with in-depth interview techniques and documentation studies, this study traces how power is exercised through a network of political, economic, military, and social organizational actors. The findings show that oligarchic dominance occurs not only through control of economic resources, but also through the co-optation of state institutions such as the legislature, bureaucracy, security forces, and media. The power structure is hierarchical-functional, with figures such as Said Amin, Tan Paulin, Haji Andre, Haji Alex, and Ismail Bolong playing complementary roles in the extractive power ecosystem. This study concludes that local oligarchs form a new historical bloc that unites formal-informal and legal-illegal power. Dismantling this dominance requires regulatory reform, political transparency, strengthening civil society, and transformation of political ethics.